Social Media Based Personal Branding Training: How Students of SMK Budi Asih Jakarta Attract Recruiters’ Attention - Yudha Pradhana; Vivitri Endah Andriani; Mira Adita Widianti; Firyal Nailah Khansa (Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid development of information and communication technology has transformed recruitment practices, with social media emerging as an essential platform for building professional identity and attracting recruiters’ attention. However, many vocational high school students still lack an understanding of how social media can be utilized for career development. This community service program aimed to enhance the understanding and skills of students at SMK Budi Asih Jakarta in developing personal branding on social media as a strategy to improve work readiness. The program employed a face-to-face training method using a participatory approach, including material presentations, interactive discussions, hands-on practice in developing professional profiles, and evaluation through pre-test and post-test assessments. Training materials covered fundamental concepts of personal branding, digital communication strategies, professional social media profile management, and the use of visual content to strengthen professional self-image. The results indicated a significant improvement in participants’ understanding of personal branding, their ability to manage professional digital identities, and increased confidence in presenting their potential in digital environments. The training contributed positively to students’ readiness to face the modern workforce, which increasingly requires digital competencies and strong professional self-presentation. This program is expected to serve as a sustainable model for developing digital competencies among vocational high school students.